Building Creative Confidence in Preservice Generalist Teachers - (:unkn) unknown (My University, 2019)
This mixed-methods research project provides a deeper understanding of creative confidence in preservice generalist teachers. This research provides insight into preservice generalist teachers’ preconceived notions and beliefs about creativity, and what aspects contribute to their creative confidence through analyzing data that reflects useful forms of preservice training for generalist teachers for them to become creatively confident leaders. This study generates strategies and recommendations for practice in teacher preparation programs and has potential to be further developed through additional study. This research contributes to a body of literature about one of art education’s continued challenges: contributing to the preparation of generalists.